Experience with fosfomycin in the treatment of complicated urinary tract infections caused by extended-spectrum beta-lactamase-producing Enterobacteriaceae. (June 2019) - Bielen, Luka; Likic, Robert
Background: The aim of this study was to evaluate the efficacy of fosfomycin in the treatment of complicated urinary tract infections (cUTIs) caused by extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae. Methods: We retrospectively evaluated 42 ambulatory patients with cUTIs caused by ESBL-producing Enterobacteriaceae at the Outpatient Internal Medicine Clinic of the University Clinical Hospital Centre Zagreb in the period from June 2012 to June 2014. ESBL production was confirmed by double disk synergy test according to Jarlier. In vitro susceptibility to fosfomycin of ESBL-producing Escherichia coli, Klebsiella pneumoniae and Citrobacter freundii isolates was tested according to the European Committee on Antimicrobial Susceptibility Testing methodology. Results: In 42 patients with cUTIs, 43 urinary pathogens susceptible to fosfomycin were isolated in the urine cultures, including 34 E. coli ESBL, seven K. pneumoniae ESBL and two C. freundii ESBL isolates. On average, patients had 2.2 complicating factors (CFs) and received 3.6 fosfomycin doses per treatment course. The overall microbiological cure was 50%, clinical cure was 71% and ESBL eradication rate was 74%. Patients with between zero and one CFs received significantly fewer fosfomycin doses than patients with two or more CFs ( p  = 0.022). Three kidney transplant patients achieved microbiological cure following prolonged fosfomycin administration. No statistically significant correlation was found between the presence of individual CFs and treatment outcome. Conclusions: Fosfomycin may be a valid option for oral treatment of cUTIs caused by ESBL-producing pathogens. The optimal duration of fosfomycin treatment for cUTIs remains to be determined.